Air-droplets as Gas Reservoir to Provide O2 to the Stored-Aqueous Droplets in Micro-channels. (2015) - Akhtar, Mahmuda; Brandhoff, Lukas; van den Driesche, Sander; Vellekoop, Michael J.
Abstract: We present a method to supply oxygen to on-chip stored aqueous droplets surrounded by oxygen-permeable fluorinated oil in micro-channels. By generating air-droplets (air-bubbles) in between the aqueous droplets, oxygen diffuses to those aqueous droplets. This is confirmed by experiments comparing the effect of nitrogen bubbles and air-bubbles. The proposed method and device are a step towards long-term on-chip cultivation of mammalian cells and aerobic bacteria growth in droplets.